Activity diversity structure-activity relationship of polysaccharides from lotus root varieties. (15th June 2018) - Yi, Yang; Lamikanra, Olusola; Sun, Jie; Wang, Li-Mei; Min, Ting; Wang, Hong-Xun
Highlights: Thirty-nine lotus root polysaccharides (LRPs) showed functional diversities. LRPs from the root peels and nodes had stronger activities than those from fleshes. The quantitative structure-activity relationship models of LRPs were proposed. Protein-binding fractions might mainly contribute to the activities of LRPs. Abstract: The in vitro activities of 39 polysaccharides from different parts of 13 lotus root varieties were evaluated and introduced into multiple linear regression analysis to explore the structure-activity relationships using their chromatographic fingerprint features as independent variables. Their 2, 2-diphenyl-1-picrylhydrazyl/hydroxyl radical scavenging abilities, ferric reducing antioxidant powers and growth-inhibitory effects against HepG2 and SGC7901 cancer cells were all diverse, with the variable-coefficients ranging from 24.49% to 87.76%, while their macrophage immunostimulatory activities evaluated by nitric oxide production and tumor necrosis factor-alpha secretion showed relatively low variations. Lotus root polysaccharides (LRPs) from the peels and nodes possessed stronger activities than those from the fleshes. Their fingerprint-activity relationship models indicated that monosaccharide composition was closely related to the activities, but not molecular weight. LRPs have health-improving potentials, and their activities can be partly predicted by the quantitative fingerprint-activity relationship model.